Designing an ESP Syllabus for International Relations: Insights from a Needs Analysis Study - Yuni Hariyanti; Junita Duwi Purwandari; Endang Setyaningsih (AL-ISHLAH: Jurnal Pendidikan, 2024)
The distinct research of ESP (English for Specific Purposes) for International Relations (IR) students is rarely explored despite the growing need of ESP for this particular group of students.  These students must demonstrate proficiency in specific language competences for a variety of purposes, including arguing, negotiating, and participating in IR-related debates. Facilitating students' ownership of the necessary capabilities is critical to ensuring that they acquire them successfully.This study aims to depict the important use of needs analysis in syllabus making for EFIR (English for International Relations). A decent preparation of the syllabus contributes to the success of the ESP implementation. In this study, the researcher involved students and expert practitioners’ intuitions as the sources of the needs analysis. The participants of this research were 108 IR students and two expert practitioners. These students were asked to filled out a questionnaire while some more-detailed interviews were conducted by involving nine stand out students that represent high, middle and low-achiever students. In addition, the four expert practitioners that consist of two lecturers and two IR graduates were interviewed to enrich the needs analysis data. All of the data were analyzed using quantitative and qualitative analysis. The finding of this study is the syllabus that can be applied for universities that provide the same ESP program for its students. The syllabus that was constructed by considering the stakeholders' needs analysis hopefully could be a useful guidance for EFIR implementation.